2021
DOI: 10.1007/s11665-021-05676-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Laser Beam Power and Scanning Speed on the Macrostructural Characteristics of AISI 316L and AISI 431 Stainless Steel Depositions Produced by Laser Cladding Process

Abstract: In the laser cladding process, control of the process parameters and knowledge of the characteristics of the materials used are essential for obtaining depositions with excellent metallurgical union, satisfactory dilution values, absence of defects, and acceptable geometric characteristics. Without such precautions, depositions can exhibit low or excess dilution, low wettability, and the presence of pores, consequently reducing the performance of the materials. The aim of the present work was to evaluate the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 44 publications
(106 reference statements)
0
9
0
Order By: Relevance
“…10c). In general, porosities are formed by the gas capture produced in the course of the fusion process, which ones couldn't have time to escape from the melt pool [24,76], as a result of the high solidi cation rate of the laser process [77].…”
Section: Macrostructural Evaluation Of the Depositions With 10% Nbcmentioning
confidence: 99%
See 2 more Smart Citations
“…10c). In general, porosities are formed by the gas capture produced in the course of the fusion process, which ones couldn't have time to escape from the melt pool [24,76], as a result of the high solidi cation rate of the laser process [77].…”
Section: Macrostructural Evaluation Of the Depositions With 10% Nbcmentioning
confidence: 99%
“…Compared to conventional coating processes such as electric arc welding overlay and plasma spraycoating, the laser deposition offers advantages, including the formation of layers with a low amount of defects, good control of the amount of energy transferred, improved quality of the coating, and simple automation ability [3][4][5][6]. Laser cladding process might in uence the shape of the bead (height, wide, and reinforce), hardness, macrostructural, and microstructural features [5,[23][24][25]. Figueredo et al [24], Moradi et al [25], and Alvarez et al [26] detailed the effect of using different metallic powder and laser cladding parameters on the nal proprieties of the depositions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…SS 431 steel, particularly, is martensitic stainless steel with remarkable mechanical properties, making it ideal for applications requiring high tensile strength and resistance to environmental factors. Understanding how to effectively cut and shape SS 431 steel is crucial in unlocking its full potential in various industries [2,3]. The unique advantage of AWJM lies in its ability to cut complex shapes without generating significant heat-affected zones or mechanical stress: a distinct advantage when working with materials such as SS 431 steel, which can be sensitive to thermal alterations.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the performance and surface quality of the coating were influenced by different processes [12,13], especially on the surface topography of the coating. Figueredo et al used different laser power and scanning rate to control the geometric structure of coating surface topography, and found that the width and dilution of deposition were greatly influenced by laser power, while the deposition height was greatly influenced by scanning speed [14]. Alvarez et al studied the influence of process parameters on surface geometric characteristics.…”
Section: Introductionmentioning
confidence: 99%